Effectiveness and cost-effectiveness of guided Internet- and mobile-based CBT for adolescents and young adults with chronic somatic conditions and comorbid depression and anxiety symptoms (youthCOACH(CD)): study protocol for a multicentre randomized controlled trial - Lunkenheimer, Frederike (Trials, 2020)
BACKGROUND: Adolescents and young adults (AYA) with chronic somatic conditions have an increased risk of comorbid depression and anxiety symptoms. Internet- and mobile-based cognitive behavioural therapy (iCBT) might be one possibility to extend the access to evidence-based treatments. Studies suggest that guided iCBT can reduce anxiety and depression symptoms in AYA. However, little is known about the effectiveness of iCBT for AYA with chronic somatic conditions and comorbid symptoms of anxiety and/or depression in routine care. Evidence on the (cost-)effectiveness of iCBT is essential for its implementation in health care. OBJECTIVES AND METHODS: This multicentre two-armed randomized controlled trial (RCT) aims to evaluate the (cost-) effectiveness of guided iCBT (youthCOACH(CD)) in addition to treatment as usual (TAU) compared to enhanced treatment as usual (TAU+) in AYA aged 12–21 years with one of three chronic somatic conditions (type 1 diabetes, cystic fibrosis, or juvenile idiopathic arthritis). AYA with one of the chronic somatic conditions and elevated symptoms of anxiety or depression (Patient Health Questionnaire [PHQ-9] and/or Generalized Anxiety Disorder [GAD-7] Screener score ≥ 7) will be eligible for inclusion. We will recruit 212 patients (2 × n = 106) in routine care through three German patient registries. Assessments will take place at baseline and at 6 weeks, 3 months, 6 months, and 12 months post-randomization. The primary outcome will be combined depression and anxiety symptom severity as measured with the PHQ Anxiety and Depression Scale. Secondary outcomes will include health-related quality of life, coping strategies, self-efficacy, stress-related personal growth, social support, behavioural activation, adjustment and trauma-related symptoms, automatic thoughts, intervention satisfaction, working alliance, and Internet usage. The cost-effectiveness will be determined, and potential moderators and mediators of intervention effects will be explored. DISCUSSION: iCBT might implicate novel ways to increase the access to evidence-based interventions in this specific population. The distinct focus on effectiveness and cost-effectiveness of youthCOACH(CD) in patients with chronic somatic conditions, as well as intervention safety, will most likely provide important new insights in the field of paediatric e-mental health. A particular strength of the present study is its implementation directly into routine collaborative health care. As such, this study will provide important insights for health care policy and stakeholders and indicate how iCBT can be integrated into existing health care systems. TRIAL REGISTRATION: German Clinical Trials Register (DRKS), DRKS00017161. Registered on 17 September 2019.